1998
DOI: 10.2307/3434063
|View full text |Cite
|
Sign up to set email alerts
|

A Case of a Laboratory Animal Feed with High Estrogenic Activity and Its Impact on in Vivo Responses to Exogenously Administered Estrogens

Abstract: We recently noted that immature rats failed to exhibit a normal uterine response to exogenously administered estradiol as assessed by both biochemical (induction of gene expression) and morphological (altered uterine and vaginal histology, and size) end points. An initial analysis suggested that this was due to a high degree ofestrogenization from a dietary source which was producing a near maximal uterotrophic response prior to hormone treatment. Subsequent chemical analysis indicated that the feed in questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 13 publications
(17 reference statements)
1
40
0
Order By: Relevance
“…For example, phytoestrogens mimic estrogen hormone action by decreasing prostate and body weight in males and females while delaying the onset of puberty presumably by blocking estrogen hormone action without impacting cyclicity [72,78]. Our findings are similar to that of a recent study (using a similar concentration of total isoflavones in the diet) that demonstrated high estrogenic activity from dietary phytoestrogens that interfered with a normal uterine response to exogenously administered estradiol [16].…”
Section: Phytoestrogens Alter Brain Morphologysupporting
confidence: 86%
See 1 more Smart Citation
“…For example, phytoestrogens mimic estrogen hormone action by decreasing prostate and body weight in males and females while delaying the onset of puberty presumably by blocking estrogen hormone action without impacting cyclicity [72,78]. Our findings are similar to that of a recent study (using a similar concentration of total isoflavones in the diet) that demonstrated high estrogenic activity from dietary phytoestrogens that interfered with a normal uterine response to exogenously administered estradiol [16].…”
Section: Phytoestrogens Alter Brain Morphologysupporting
confidence: 86%
“…In this diet, soymeal is the first ingredient listed in the formulation (and the diet does not contain alfalfa). The total isoflavone concentration of the diet we used is similar to that reported in a separate study (approximately 350 mg/g diet of total isoflavones) that was found to have estrogenic activity in rodents [16]. We have compared the influence of this commercial diet to that of a custom diet with very low concentrations of phytoestrogens (Ziegler Brothers, Gardner, PA, USA) [24,105].…”
Section: Phytoestrogen Dietsmentioning
confidence: 53%
“…This phytoestrogen has 10 2 -fold greater estrogenicity (Bickoff et al, 1962) than soy isoflavones, and major rodent diet manufacturers now offer phytoestrogen-reduced diets that exclude alfalfa as an ingredient. It was pointed out recently that immature rats unwittingly fed a rodent diet formulated with soy-meal and alfalfa had a near maximal uterotrophic stimulation and consequently failed to show the usual biochemical and morphological responses to exogenously administered estradiol (Boettger-Tong et al, 1998). The diet's composition had been reformulated without any notice to researchers using the feed, triggering months of troubleshooting.…”
mentioning
confidence: 99%
“…Such effects have tremendous implications for animal experiments, particularly when biochemical or morphological end-points are being measured that may be influenced by the hormonal or nonhormonal properties of isoflavones (Boettger-Tong et al, 1998;Drane et al, 1975). Coumestrol, a component of alfalfa (Knuckles et al, 1976) and still present in some commercial rodent diets, influences uterine growth (Ashby et al, 1999;, accelerates vaginal opening , and causes long-term effects on reproductive cycling and behavior (Whitten et al, 1995).…”
mentioning
confidence: 99%
“…It was found that soy isoflavones present in feed at high amounts interfere with the value of animal models and with experimental results (10). An example of this was a decreased sensitivity of immature rats (5) and hamsters (20) in the uterotrophic bioassay.…”
Section: Discussionmentioning
confidence: 99%